Effect of Chlorella vulgaris supplementation with eccentric exercise on serum interleukin 6 and insulin resistance in overweight men - Samadi, Mohammad; Shirvani, Hossein; Shafeie, Ali Akbar (Sport sciences for health, 2020)
Purpose Overweight can lead to the down-regulation of insulin sensitivity and cytokine profile. In this regard, non-pharmacological interventions such as exercise and supplementation are recommended. Therefore, the aim of this study was to investigate the synergistic effect of Chlorella vulgaris supplementation with acute eccentric exercise on serum levels of interleukin-6 and insulin resistance in overweight men. Methods Thirty subjects (aged 22.8 ± 2.1 years, BMI 27.1 ± 9.6 kg/m 2 ) were randomly divided into three equal groups: exercise [just perform acute eccentric exercise test (AEE)], Chlorella vulgaris (for 7 days and then AEE), placebo (for 7 days and then AEE). Blood sampling was performed in 4 stages: day 1 (before supplementation) and day 7 (after supplementation), after AEE and 24 h after AEE. Subjects of the supplement group received Chlorella vulgaris supplement (300 mg) four times daily for 1 week, and the placebo group consumed similar dextrose tablets. Exercise groups just perform AEE. AEE test included a 20-min treadmill run at a speed of 9 km/h with a negative 10% slope. Serum levels of IL-6, insulin, and glucose were measured by Elisa kit. Also, the hip circumference and knee range of motion (ROM) was measured at four stages. Results At the end of the study, there was a significant decrease in IL-6 levels in the Chlorella vulgari s group compared to the other two groups at 24 h after AEE test ( P < 0.01). There was also a significant decrease in insulin resistance levels in the supplement group compared to the other two groups at 24 h after AEE test ( P < 0.02). Also, the knee ROM decreased significantly in all three groups ( P < 0.05). Conclusion Chlorella vulgaris with acute eccentric exercise can have a more modulating effect on serum IL-6, insulin resistance and other characteristics in overweight men compared to acute eccentric exercise without chlorella.